Migration of the Plastic Clips of the Cystic Ducts to the Bile Duct Post-Laparoscopic Cholecystectomy: A Case Report - Limas, Peter Ian; Barlian Sutedja (Sriwijaya Journal of Surgery, 2024)
Introduction: Migration of the cystic duct clip into the common bile duct is a rare but significant complication following laparoscopic cholecystectomy. This condition can cause biliary obstruction, cholangitis, and gallstone formation. Case presentation: A 60-year-old man presented with symptoms of cholangitis. His medical history included laparoscopic cholecystectomy with choledochoscopy and intraoperative cholangiography. MRCP showed stones and sludge in the common bile duct (CBD), but did not identify a migrated clip. Endoscopic retrograde cholangiopancreatography (ERCP) successfully extracted the migrated clip causing the obstruction. Conclusion: Migration of the clip into the common bile duct should be considered in the differential diagnosis of biliary obstruction following laparoscopic cholecystectomy. Early identification through careful imaging and ERCP can facilitate appropriate management and prevent further complications.